Theoretical analysis and fabrication of tapered fiber - Harun, Sulaiman Wadi; Lim, K.S.; Tiong, C.K.; Dimyati, K.; Ahmad, Harith (Elsevier, 2013)
Adiabaticity criteria and optimal shapes for tapered fiber are theoretically analyzed. In the analysis, it is discovered that a narrower taper waist can be achieved by using a small hot-zone length or increases the elongation distance. The tapered fiber fabrication based on flame brushing technique is then demonstrated using a homemade fiber tapering rig. The heat source comes from an oxy-butane torch with a flame width of 1 mm. Two stepper motors are incorporated in the rig to control the movement of the torch and translation stage. A biconical tapered fiber with a waist diameter as small as 400 nm can be achieved with the rig. To achieve low loss tapered fibers, the shape of the taper should be fabricated according to adiabaticity criteria, whereby the longer transition length is desirable. Tapered fibers with linear and decaying-exponential profiles have been successfully fabricated.